Upaya Dalam Merencanakan Penerapan Pajak PPh 21 Sebagai Langkah Pengefesiensian Pajak Penghasilan - Endang Suriyani Munthe; Risa Lidia; Afni Haryanti Harahap; Dini Vientiany (CV. ITTC INDONESIA, 2024)
Tax subjects are individuals or entities who have an obligation to pay tax on the income they receive. By developing existing data, we can gain a deeper understanding of the various categories of tax subjects as well as the types of income that are tax objects within the framework of PPh Article 21. The mechanism for withholding Income Tax Article 21 (PPh Article 21) is an important procedure in the Indonesian tax system . HPP Law No.7 of 2021 regulates the latest PTKP which applies to certain tax years. Here are the details. The method used in this research is the literature review method. The study is carried out by looking for relevant sources through reading, classifying all descriptions, data, or information contained in the books of the figure or other authors, then confirming each other. The latest PTKP according to the law is for taxpayers without ptkp dependents: IDR 54,000,000 each year, married taxpayers with 1 ptkp dependent: IDR 63,000,000 each year. Income Tax Article 21 is a tax that is withheld by income providers (usually employers) from the income of employees or other income recipients. This process involves several stages, including calculating net income, using the PPh Article 21 rate table, withholding tax, and providing proof of withholding to employees.